Management of Peyronie's Disease by Dermal Grafting - Nikoobakht, Mohammad Reza; Mehrsai, Abdolrasoul; Pourmand, GH; Jaladat, Hooman; Nasseh, Hamid Reza (Urology Journal, 2009)
Purpose: To evaluate the results of plaque excision and dermal grafting in Peyronie’s disease. Materials and Methods: Twenty seven patients were scheduled to undergo plaque excision and dermal grafting for Peyronie’s disease. Potency, bending of erected penis, and having painful erection were evaluated in patients before and after operation. To evaluate erectile dysfunction, we used International Index of Erectile Function (IIEF) by interviewing the patients and filling questionnaires by their partners. Doppler ultrasonography was used to determine the vascular competence of penis before and after operation in 15 patients. Results: The disease was more prevalent between the ages of 40 and 60 years. Plaques were located as follows: dorsal in 18, right lateral in 6 and left lateral in 3. Mean plaque size was 11 (range 5 to 18) mm. After plaque excision and dermal grafting, penile deformity, erectile dysfunction, and painful erection had remained yet in 4 (15%) out of 27, 3 (16%) out of 19, and 3 (14%) out of 22, respectively. Doppler ultrasonographic study in 15 patients revealed improvement in peak systolic velocity (P < 0.01). In addition, a decrease in end diastolic velocity was noted also that was not significant statistically (P = 0.26). Resistive index did not improve after operation. Conclusion: This procedure showed significant improvement in penile deformity (85% of cases), erectile dysfunction (84% of cases) and painful erection (86% of cases). We recommend plaque excision and dermal grafting as an effective procedure in treating Peyronie’s disease.